Imaging in rectal cancer with emphasis on local staging with MRI - Arya, Supreeta; Das, Deepak; Engineer, Reena; Saklani, Avanish (Indian Journal of Radiology and Imaging, 2015)
Imaging in rectal cancer has a vital role in staging disease, and in selecting and optimizing treatment planning. High-resolution MRI (HR-MRI) is the recommended method of first choice for local staging of rectal cancer for both primary staging and for restaging after preoperative chemoradiation (CT-RT). HR-MRI helps decide between upfront surgery and preoperative CT-RT. It provides high accuracy for prediction of circumferential resection margin at surgery, T category, and nodal status in that order. MRI also helps assess resectability after preoperative CT-RT and decide between sphincter saving or more radical surgery. Accurate technique is crucial for obtaining high-resolution images in the appropriate planes for correct staging. The phased array external coil has replaced the endorectal coil that is no longer recommended. Non-fat suppressed 2D T2-weighted (T2W) sequences in orthogonal planes to the tumor are sufficient for primary staging. Contrast-enhanced MRI is considered inappropriate for both primary staging and restaging. Diffusion-weighted sequence may be of value in restaging. Multidetector CT cannot replace MRI in local staging, but has an important role for evaluating distant metastases. Positron emission tomography-computed tomography (PET/CT) has a limited role in the initial staging of rectal cancer and is reserved for cases with resectable metastatic disease before contemplating surgery. This article briefly reviews the comprehensive role of imaging in rectal cancer, describes the role of MRI in local staging in detail, discusses the optimal MRI technique, and provides a synoptic report for both primary staging and restaging after CT-RT in routine practice.
Keywords: Imaging; local staging; MRI; staging rectal cancer